Deadly Medicine : creating the master race - United States Holocaust Memorial Museum
German eugenics, 1890-1933 / by Sheila Faith Weiss -- International eugenics / by Daniel J. Kevles -- Nazi sterilization and reproductive policies / by Gisela Bock -- The "science of race" / by Benoit Massin -- Nazi "euthanasia" programs / by Michael Burleigh -- From "euthanasia" to the "final solution" / by Henry Friedlander -- Reflections of a German scientist / by Benno Müller-Hill -- Chronology